Growth and Yield of Elephant Foot Yam under Integrated Nutrient Management (INM) in Alfisols - Nedunchezhiyan, M (JOURNAL OF ROOT CROPS, 2015)
The field experiment was carried out for consecutive two years during 2011-12 and 2012-13 to study the effect of integrated nutrient management practices on elephant foot yam. The experiment was conducted in randomized block design with three replications. The treatment consisted of N-P2O5-K2O 60-60-60, 80-60-80 and 100-60-100 kg/ha, the above treatments in combination with FYM 10 t/ha, FYM @ 25 t/ha and control. The results revealed that application of FYM @ 25 t/ha recorded longer pseudostem, higher canopy spread, pseudostem diameter and no. of leaflets per plant. However, yield attributes and corm yield were found significantly higher with the application of N-P2O5-K2O 100-60-100 kg/ha along with FYM 10 t/ha. The nitrogen and potassium uptake was highest in the treatment FYM 10 t/ha along with 100-60-100 NPK kg/ha whereas maximum phosphorus uptake was noticed in the treatment FYM 25 t/ha. The post-harvest soil nutrient status revealed that maximum soil nitrogen and phosphorus was available in FYM 10 t/ha + N-P2O5-K2O 100-60-100 kg/ha and potassium was in N-P2O5-K2O 100-60-100 kg/ha.